Evaluation of a point-of-care immunoassay test kit `StrongStep' for cryptococcal antigen detection - Mpoza, Edward; Mukaremera, Liliane; Akampurira, Andrew; Mahsa, Abassi (PLoS One, 2018)
HIV-associated cryptococcal meningitis is the leading cause of adult meningitis in Sub-Saharan Africa, accounting for 15%–20% of AIDS-attributable mortality. The development of point-of-care assays has greatly improved the screening and diagnosis of cryptococcal disease. We evaluated a point-of-care immunoassay, StrongStep (Liming Bio, Nanjing, Jiangsu, China) lateral flow assay (LFA), for cryptococcal antigen (CrAg) detection in cerebrospinal fluid (CSF) and plasma.